Rancang Bangun Aplikasi Pemberian Usulan Remisi Narapidana Pada Rumah Tahanan Kelas IIB Bangil - Jati, Kelik Hendra; Setyawan, Henry Bambang; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: Bangil IIB class State Detention Center (Rutan) is a Technical Implementer Unit of the Regional Office of Social Matters under the Ministry of Law and Human Rights East Java Province. In general, detention center as a development house for the citizen who commits an infraction in accordance with article 1 Number 12 of Law 1995 which describes about social matters. Bangil IIB Class Detention Center which is located at Mango st. 2 Bangil has 39 employees and the number of prisoners in December of 2013 for about 355 people, consisting of 185 inmates and 170 detentions. There is a process of giving proposals remission granted to prisoners in the detention center each year for those who have been running the requirements to obtain remission. In the process of making the proposed remission, the officers are required to calculate remission proposals accurately one by one prisoner, it is becoming a problem in getting the proposal which are calculated manually. Frequent occurrence of errors in granting remission proposal has impact on the inaccurate date of the prisoners will be free. From the existing problems, then a proposal about computing applications is made based on remission desktop with the title